Regional and remote occupational therapy: A preliminary exploration of private occupational therapy practice. Issue 4 (24th June 2013) - Merritt, Judith; Perkins, David; Boreland, Frances
<x xml:space="preserve">Abstract</x> Background/aim Private providers of Medicare funded services are an integral part of the Australian primary health‐care system. Evidence on private occupational therapy practice in rural and remote Australian settings is sparse. Methods Providers of private occupational therapy services in outer regional and remote areas were surveyed regarding location and type of services provided, practice models and demographics. Descriptive statistics were used to summarise the findings. Results Thirty‐seven respondents completed the survey. In remote areas a number of occupational therapy services are not provided and no practices are based in very remote towns. One quarter of respondents visit at least five towns each week and one third had other paid employment. Nearly half indicated they will leave private practice within the next five years and nearly one third believed they could not sustain their practice. Medicare Chronic Disease Management was the main income source of only around half the respondents. Conclusions There is a potential market failure of private occupational therapy in rural and remote areas, impacting on people who need these services and on workforce replacement. Contributing factors include population imbalance between cities and regional/remote areas, financial implications where only face‐to‐face contact is paid for and low incomes and levels of health insurance in regional/remote areas. Potential strategies include addressing the lack of reimbursement for travel, enabling private providers to overcome barriers to providing student placements and recognising rural practice as a specialist field.